Assessing Household Awareness of Indoor Air Pollution in Cagayan de Oro City: Implications for Health Promotion - Araune, Paolo; Vera, Glenda De; Agudong, Shane Stiffany; Abarquez, Joea Carmel; Apag, Hannah Catherine; Basalo, Paul Kenneth; Batayola, Alyana Kyle; Co, Janet; Daanoy, Mary Ann; Dante, John Ray; Ebale, Nicolle; Estonilo, Cindy Mae; Fabela, Stephen Christian; Fullo, Justine Joy (International Journal of Nursing and Health Services (IJNHS), 2024)
Background & Aim: Indoor air pollution is a significant health threat, yet public awareness remains low, particularly in regions like the Philippines. This study assessed household awareness of indoor air pollution sources in a barangay in Cagayan de Oro City. Using the Health Promotion Model by Nola Pender and the Environmental Theory by Florence Nightingale, it sought to understand factors influencing awareness and inform health programs addressing indoor air pollution in the community. Methods & Materials: This study used a descriptive correlational design to explore how demographic factors influence awareness of indoor air pollution sources in a barangay in Cagayan De Oro City. Surveys, translated into the local language and validated through pilot testing, were administered to 264 randomly selected respondents. Statistical analyses, including T-tests and ANOVA, were conducted to assess associations between demographic variables and awareness levels. Results: Significant differences were observed in respondents' awareness levels of indoor air pollution sources across age groups, with middle-aged individuals demonstrating the highest awareness. Females exhibited consistently higher awareness compared to males across all pollution sources. Educational attainment influenced awareness levels, with postgraduates showing the highest awareness. Conclusion: The study revealed significant correlations between demographic factors and respondents' awareness of indoor air pollution sources. Age, gender, and educational attainment influence awareness levels, motivating individuals to prioritize proper ventilation for health preservation. Recommendation: Clinical practitioners should prioritize health education programs targeting middle-aged individuals, females, and those with higher educational attainment levels in addressing indoor air pollution awareness, emphasizing the importance of proper ventilation practices for health preservation and promoting healthier indoor environments in communities